Infliximab for the treatment of intravenous immunoglobulin resistant Kawasaki disease complicated by coronary artery aneurysms: a case report - Klein Nigel J; Gnanapragasam James; Eleftheriou Despina; Brogan Robert J; Brogan Paul A (BMC, 2009)
Abstract This case report describes an 8 year old boy with IVIG resistant Kawasaki disease complicated by severe bilateral coronary artery aneurysms successfully treated with infliximab, a monoclonal antibody against tumour necrosis factor alpha.